Do anthropometrical indices correlate with pulse oximetry among children attending a private hospital in Enugu? - Josephat M Chinawa; Bartholomew F Chukwu; Awoere T Chinawa (Journal of Medical Sciences, 2019)
Background: Pulse oximetry remains the most common investigation in pediatric cardiology as it acts as a window to unravel most abnormalities in cardiac functions and structure. Objectives: The objective of this study was to determine what is actually the normative pulse oximetry reading among children and to determine if anthropometry has any effect on pulse oximetry. Methodology: A cross-sectional prospective study in which pulse oximetry readings were ascertained among healthy children attending a private clinic in Enugu over a 3-year period. Data Analysis: Data were analyzed using Stata 10 software (STATA 10, College Station, Texas, USA: Stata [Corp]) Means and 95% confidence intervals were calculated for all the individuals. The level of statistical significance was considered P < 0.05. Results: A total of 349 individuals were recruited consecutively. The median value of oxygen saturation (SpO2) was 98% (93%–99%). Females had a significantly higher SpO2 than the males (Wilcoxon-Mann–Whitney test, Z = 2.064, P = 0.04). There was a positive correlation between the SpO2 and age, weight, and height of the patients. Of these anthropometry, height is the most correlated with SpO2. On the other hand, there was a negative correlation between SpO2 and heart rate of the subjects (rho = −0.1845, P = 0.0005). There was no correlation between SpO2 and patient's body mass index (BMI). Conclusion: The normal oximetry reading among children in this study is 98% with a positive correlation with age, weight, and height and a negative correlation with heart rate but no correlation with patient's BMI.